How do FTAs affect exporting firms in Thailand? - Ganeshan Wignaraja; Rosechin Olfindo; Wisarn Pupphavesa; Jirawat Panpiemras; Sumet Ongkittikul (Asian Development Bank Institute (ADBI), 2010)
Thailand - an outward-oriented regional production hub - is one of East Asia's most active users of free trade agreements (FTAs) as an instrument of commercial policy. By December 2009, Thailand had 11 concluded FTAs, and more were either under negotiation or proposed. Thai trade negotiators have striven to secure market access via FTAs, but little is known on how FTAs actually affect exporting firms. A survey of 221 exporters in leading sectors forms the basis for the first systematic study of the business impact of FTAs in Thailand. Key findings are as follows: (i) 24.9% of respondents used Thai FTAs as of 2007-2008, and this figure seems set to rise; (ii) 45.9% of respondents said that FTAs had influenced their business plans; (iii) 26.2% of firms felt that dealing with multiple rules of origin adds to business costs, and this is estimated to be less than 1% of export sales; (iv) more than half the sample firms have consulted with government and business associations on FTAs; and (v) a significant demand existed for business development services to adjust to FTAs, particularly for small and medium enterprises (SMEs). The findings suggest that Thailand should refine its FTA strategy to take better advantage of regional trade agreements. The study concludes with specific recommendations to improve business awareness of FTAs, encourage greater utilization of FTA preferences, increase competitiveness of local firms, and mitigate the potential effect of multiple rules of origin.
Keywords: F1; F15; O24; 330; Freihandelszone; Handelsregionalismus; Exportindustrie; Außenwirtschaftspolitik; Thailand